A meta-aramid-based separator and a preparation method and application thereof

CN122696923BActive Publication Date: 2026-10-27TAYHO BATTERY MATERIALS TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611201934.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-27
Estimated Expiration
2046-08-10

AI Technical Summary

Technical Problem

[0004]但芳纶涂覆基膜的复合结构也具有难以突破的固有缺陷

Benefits of technology

本发明公开了一种间位芳纶基隔膜及其制备方法和应用,所述间位芳纶基隔膜以间位芳纶(PMIA)为基体、以经表面改性的对位芳纶(PPTA)纳米纤维为增强相,形成全芳纶一体化多孔膜结构,从根本上避免了传统聚烯烃基膜和芳纶涂覆复合结构因基膜熔融坍塌导致的热失控风险以及涂覆层开裂脱落等问题。该隔膜兼具优异的耐高温性能、力学强度和离子传输效率,破膜温度不低于240℃,180℃热收缩率不超过10%,离子电导率甚至可达到0.4mS/cm以上,且制备过程简便、工艺参数可控,具有良好的工业化应用前景,能够满足高能量密度锂离子电池、钠离子电池等储能装置对隔膜性能的严苛要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122696923B_ABST
    Figure CN122696923B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of battery materials, and particularly relates to a meta-aramid-based separator, a preparation method and application thereof, the preparation method being: PPTA nanofibers are added into an inorganic alkali solution for alkali etching activation, and then washed and dried; the PPTA nanofibers are added into an organic acid aqueous solution for organic acid grafting reaction, and then washed and dried to obtain modified PPTA nanofibers; the modified PPTA nanofibers are added into a PMIA solution containing a dispersant, and are subjected to sufficient dispersion treatment to obtain a coating liquid; the coating liquid is uniformly coated on a release film, water vapor is sprayed on the film to form pores, and then the film is sequentially subjected to a coagulation bath, a water bath, drying and winding, and then the aramid film is peeled off from the release film, and the aramid film is subjected to hot pressing to obtain the meta-aramid-based separator. The meta-aramid-based separator has excellent electrolyte wettability and heat-resistant stability, and excellent ion transmission performance, and is convenient for matching high-energy-density batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a meta-aramid-based separator, its preparation method, and its application, belonging to the field of battery materials technology. Background Technology

[0002] As a core component of lithium-ion batteries, the performance of the battery separator directly determines the battery's safety, cycle life, and rate capability. With the widespread application of 811-series ternary batteries and high-nickel cathode materials, battery energy density continues to increase, placing higher demands on the separator's high-temperature resistance, mechanical strength, and ion transport efficiency. Among these, meta-aramid (poly(m-phenylene isophthalamide),) exhibits excellent electrolyte wettability and chemical stability due to its stable structure formed by strong hydrogen bonds between its molecular chains. Separators made from it can effectively block electron conduction between the positive and negative electrodes while providing a channel for lithium-ion transport, showing significant application potential in the field of power batteries.

[0003] To address the poor high-temperature resistance of traditional polyolefin separators (PE / PP), an aramid-coated base film composite product has been developed. This product utilizes the high-temperature resistance of aramid, coated with a meta-aramid layer, to compensate for the deficiencies of polyolefin materials. Compared to pure PE separators, the aramid-coated base film exhibits superior thermal shrinkage performance; simultaneously, the aramid coating mitigates the swelling and erosion of the base film by the electrolyte.

[0004] However, the composite structure of aramid-coated base films also has inherent drawbacks that are difficult to overcome. Firstly, the thermal safety limit is limited. The aramid coating can only play a supplementary role in thermal insulation. When the battery shows signs of thermal runaway and the temperature rises above 150°C, the polyolefin base film will melt and collapse due to reaching its melting point, causing the separator to lose its barrier function and failing to meet the thermal runaway protection requirements of 811 series batteries above 180°C. Secondly, there is the issue of interfacial compatibility. The bonding between the non-polar polyolefin base film and the polar aramid coating mainly relies on physical adsorption. Under the mechanical stress of battery charge-discharge cycles, the coating layer is prone to cracking and peeling. Furthermore, ion transport efficiency is also limited by the structure. The dense aramid coating layer and the interfacial gaps between the base film and the coating increase the tortuosity of the lithium-ion migration path.

[0005] Therefore, solving the structural defects of the coated base film and achieving a synergistic improvement in mechanical strength and electrochemical performance has become a key technical requirement in the field of high-performance separators. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a meta-aramid-based separator, its preparation method, and its application. The meta-aramid-based separator exhibits excellent electrolyte wettability and thermal stability, as well as superior ion transport performance. The separator coating thickness is adjustable, making it easy to match the actual working requirements of high-energy-density batteries and facilitate industrial-scale production.

[0007] The technical solution of this invention to solve the above-mentioned technical problems is as follows: a method for preparing a meta-aramid-based separator, wherein the preparation method is as follows: S1. Alkali etching activation: PPTA nanofibers are added to an inorganic alkaline solution for alkaline etching activation, followed by washing and drying; S2, Organic acid grafting: The PPTA nanofibers treated in step S1 are added to an organic acid aqueous solution to carry out an organic acid grafting reaction, and then washed and dried to obtain modified PPTA nanofibers. S3. Preparation of coating solution: Add the modified PPTA nanofibers to the PMIA solution containing the dispersant and perform sufficient dispersion treatment to obtain a uniform composite coating solution. S4. Coating and film formation: The composite coating liquid is uniformly coated on the release film, water vapor is sprayed to create holes, and then the film is sequentially passed through a coagulation bath, a water bath, drying, and winding. The aramid film is peeled off from the release film, and the aramid film is hot-pressed to obtain the meta-aramid-based separator.

[0008] Further, in step S1, the inorganic alkaline solution is at least one of sodium hydroxide aqueous solution and potassium hydroxide aqueous solution, and the mass concentration of the inorganic alkaline solution is 5-15 wt%. In step S1, during the alkaline etching and activation process, the temperature is 60-80℃, and the mixture is stirred at a constant temperature for 2-4 hours.

[0009] Further, in step S2, the organic acid aqueous solution is at least one selected from citric acid aqueous solution, tartaric acid aqueous solution, and 1,4-phthalic acid aqueous solution, and the mass concentration of the organic acid aqueous solution is 10-20 wt%. In step S2, the organic acid grafting reaction is completed by stirring under reflux for 3-6 hours.

[0010] Furthermore, in step S3, the solid content of the PMIA solution is 5-20 wt%.

[0011] Further, in step S3, the dispersant is at least one of polyvinylpyrrolidone, sodium dodecylbenzenesulfonate, and Tween 80; the amount of the dispersant added is 1-5 wt% of the PMIA mass.

[0012] Further, in step S3, the amount of modified PPTA nanofibers added is 5-20 wt% of the PMIA mass.

[0013] Further, in step S3, the dispersion treatment includes high-speed shear dispersion and ultrasonic dispersion performed sequentially; the high-speed shear dispersion has a rotation speed of 15000-20000 rpm and a dispersion time of 20-30 min; the ultrasonic dispersion has a power of 300-500 W and a dispersion time of 30-60 min, and the ultrasonic dispersion is performed under ice-water bath conditions.

[0014] Furthermore, in step S4, the conditions for the water vapor spray film pore formation are: water vapor quantity of 0.05-0.2 g / cm², and steam action time of 5-20 s.

[0015] The present invention also discloses a meta-aramid-based separator, wherein the meta-aramid-based separator is prepared according to the preparation method described in the present invention.

[0016] The present invention also discloses an application of a meta-aramid-based separator, which is used in a battery.

[0017] The beneficial effects of this invention are: This invention discloses a meta-aramid-based separator, its preparation method, and its applications. The meta-aramid-based separator uses meta-aramid (PMIA) as the matrix and surface-modified para-aramid (PPTA) nanofibers as the reinforcing phase, forming an integrated aramid porous membrane structure. This fundamentally avoids the risks of thermal runaway caused by the melting and collapse of the base membrane and the cracking and peeling of the coating layer in traditional polyolefin-based membranes and aramid-coated composite structures. This separator possesses excellent high-temperature resistance, mechanical strength, and ion transport efficiency. Its rupture temperature is not lower than 240℃, its thermal shrinkage rate at 180℃ is less than 10%, and its ionic conductivity can even reach above 0.4 mS / cm. Furthermore, the preparation process is simple and the process parameters are controllable, showing good prospects for industrial application and meeting the stringent performance requirements of high-energy-density lithium-ion batteries, sodium-ion batteries, and other energy storage devices.

[0018] In the method for preparing meta-aramid membranes of this invention, PPTA nanofibers are surface modified through a two-step process of "alkali etching activation" and "organic acid grafting," forming a close synergistic relationship between the two steps. Alkali etching activation utilizes an inorganic alkaline solution to break the amide bonds on the PPTA surface, introducing polar groups such as carboxyl and hydroxyl groups. Simultaneously, it etches a micro-rough structure on the fiber surface, providing sufficient active sites and physical anchoring points for subsequent grafting reactions. Organic acid grafting utilizes the esterification reaction between polycarboxylic acids and hydroxyl groups on the fiber surface or the formation of hydrogen bonds with amino groups, further grafting a large number of carboxyl groups onto the fiber surface. Without the pre-construction of active sites through alkali etching activation, the grafting density of organic acid grafting would be extremely low due to a lack of reaction sites. Without the secondary scale-up of organic acid grafting, the number of polar groups introduced by alkali etching activation is limited, making it difficult to fully meet the chemical bonding density required for interfacial bonding. The combined treatment of "alkali etching activation" and "organic acid grafting" significantly increases the carboxyl content on the surface of modified PPTA nanofibers and greatly enhances their polarity, ultimately achieving a strong chemical bond and / or hydrogen bond with the PMIA matrix, thus solving the technical problem of poor interfacial compatibility between nanofibers and the matrix.

[0019] More specifically, in the preparation method described in this invention, the stepwise dispersion method of high-speed shearing and ultrasound, combined with the modification-avoidance treatment of alkaline etching activation and organic acid grafting, helps to ensure the efficient dispersion and sufficient anchoring of the reinforcing phase in the matrix. Surface modification increases the surface polarity of PPTA fibers and reduces their tendency to aggregate, creating favorable conditions for high-speed shear dispersion, enabling the shear force to effectively break up micron-sized agglomerates. Ultrasonic dispersion under ice-water bath conditions further utilizes the cavitation effect to break up nano-sized agglomerates and fully releases the active groups exposed on the surface of the grafted fibers. Ultimately, uniform dispersion and interfacial anchoring of modified PPTA nanofibers in the PMIA matrix are achieved, resulting in better membrane performance uniformity and effectively avoiding problems such as local mechanical weakness and disordered ion transport pathways caused by fiber agglomeration.

[0020] In the preparation method described in this invention, water vapor spraying induces the PMIA phase transformation to form a porous structure. The modified PPTA nanofibers, uniformly dispersed in the matrix, with their ultra-high strength and rigidity, construct a stable three-dimensional support framework around the pore walls. This effectively resists the shrinkage stress caused by capillary forces during pore formation, preventing pore wall collapse and structural shrinkage. This allows the membrane to achieve high porosity while maintaining excellent mechanical strength and dimensional stability. The meta-aramid-based membrane described in this invention maintains excellent mechanical strength while significantly increasing porosity, and exhibits extremely low thermal shrinkage and a significantly increased membrane rupture temperature.

[0021] The all-aramid integrated structure constructed in this invention significantly improves the electrolyte wettability and ion transport performance of the separator. The numerous polar groups, such as carboxyl groups, grafted onto the surface of the modified PPTA nanofibers enhance the separator's affinity for polar electrolytes, resulting in a significantly increased liquid absorption rate. Simultaneously, the integrated structure eliminates the interfacial gap between the coating and the base film in traditional coated films, reducing the tortuosity of the lithium-ion migration path. Combined with a uniform pore structure distribution, this leads to a significant improvement in ionic conductivity. Furthermore, the all-aramid system endows the separator with extremely high thermal stability, meeting the stringent requirements of 811 series high-nickel batteries for thermal runaway protection above 180°C. Attached Figure Description

[0022] Figure 1 This is an electron microscope image of the diaphragm prepared in Example 1. Detailed Implementation

[0023] The specific embodiments of the present invention will be described in detail below. The present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed herein.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used is for describing particular embodiments only and is not intended to limit the invention.

[0025] A method for preparing a meta-aramid-based separator, wherein the preparation method comprises: S1. Alkali etching activation: PPTA nanofibers are added to an inorganic alkaline solution for alkaline etching activation. This breaks the amide bonds on the PPTA surface and introduces polar groups such as -COOH and -OH. At the same time, the surface is etched to form a micro-rough structure to increase the specific surface area. Then, the nanofibers are repeatedly washed with deionized water until pH=7 to avoid residual inorganic alkali affecting the dissolution of PMIA. The nanofibers are then vacuum dried at 70-80℃ for 3-4 hours. S2, Organic Acid Grafting: The PPTA nanofibers treated in step S1 are added to an organic acid aqueous solution for organic acid grafting reaction. The mixture is refluxed and stirred. The -COOH of the organic acid reacts with the -OH on the PPTA surface through esterification or forms hydrogen bonds with -NH2, further enhancing the surface polarity and interfacial bonding. After post-treatment, the mixture is filtered, washed until neutral, and vacuum dried at 80°C to obtain modified PPTA nanofibers. S3. Preparation of coating solution: Add the modified PPTA nanofibers to the PMIA solution containing the dispersant and perform sufficient dispersion treatment to obtain a uniform composite coating solution. S4. Coating and film formation: The composite coating liquid is uniformly coated on the release film, water vapor is sprayed to create holes, and then the film is sequentially passed through a coagulation bath, a water bath, drying, and winding. The aramid film is peeled off from the release film, and the aramid film is hot-pressed to obtain the meta-aramid-based separator.

[0026] More specifically, in step S1, the ratio of PPTA nanofibers to inorganic alkali solution is PPTA nanofibers: inorganic alkali aqueous solution = 1g: 30mL. In step S2, the ratio of PPTA nanofibers to organic acid aqueous solution is PPTA nanofibers: organic acid aqueous solution = 1g: 30mL.

[0027] More specifically, the PPTA nanofibers used in the embodiments of the present invention have a diameter of 50-200 nm and a length of 0.1-1 mm.

[0028] Specifically, in step S1, the inorganic alkaline solution is at least one of sodium hydroxide aqueous solution and potassium hydroxide aqueous solution, and the mass concentration of the inorganic alkaline solution is 5-15 wt%. In step S1, during the alkaline etching and activation process, the temperature is 60-80℃, and the mixture is stirred at a constant temperature for 2-4 hours.

[0029] Specifically, in step S2, the organic acid aqueous solution is at least one selected from citric acid aqueous solution, tartaric acid aqueous solution, and 1,4-phthalic acid aqueous solution, and the mass concentration of the organic acid aqueous solution is 10-20 wt%. In step S2, the organic acid grafting reaction is completed by stirring under reflux for 3-6 hours.

[0030] Preferably, the mass concentration ratio of the inorganic alkaline solution to the organic acid aqueous solution is 1:(1.3-2.0).

[0031] Specifically, in step S3, the solid content of the PMIA solution is 5-20 wt%.

[0032] More specifically, the specific process of step S3 is as follows: DMAC is added to the PMIA stock solution (poly(m-phenylene isophthalamide), solvent is DMAC) for dilution, then a dispersant is added and stirred, and then surface-modified PPTA nanofibers are added; the first step is to use high-speed shear dispersion to break up the large fiber aggregates ≥1μm; the second step is to cool in an ice-water bath (to prevent solvent evaporation), and then use ultrasonic dispersion to break up the small nano-aggregates of 100-500nm, so as to obtain a uniform composite coating solution.

[0033] More specifically, the PMIA stock solution used in the embodiments of the present invention has a viscosity of 400-600 Po (25°C) and a polymer molecular weight of 10-12 W in the PMIA stock solution.

[0034] Specifically, in step S3, the dispersant is at least one of polyvinylpyrrolidone, sodium dodecylbenzenesulfonate, and Tween 80; the amount of the dispersant added is 1-5 wt% of the PMIA mass.

[0035] Specifically, in step S3, the amount of modified PPTA nanofibers added is 5-20 wt% of the PMIA mass.

[0036] Specifically, in step S3, the dispersion process includes high-speed shear dispersion and ultrasonic dispersion performed sequentially; the high-speed shear dispersion has a rotation speed of 15,000-20,000 rpm and a dispersion time of 20-30 min; the ultrasonic dispersion has a power of 300-500 W and a dispersion time of 30-60 min, and the ultrasonic dispersion is performed under ice-water bath conditions.

[0037] In this embodiment of the invention, the equipment used for high-speed shear dispersion processing is a planetary mixer (Dongguan Langling Machinery Co., Ltd., LMT-300).

[0038] Specifically, in step S4, the conditions for creating holes by spraying water vapor film are: water vapor quantity of 0.05-0.2 g / cm², and steam action time of 5-20 s.

[0039] Preferably, the amount of modified PPTA nanofibers added is 15 wt% of the PMIA mass; the amount of water vapor is 0.15 g / cm², and the steam treatment time is 15 s.

[0040] Uniformly dispersed PPTA nanofibers form an effective "three-dimensional support framework" within the PMIA matrix. This framework resists the shrinkage stress caused by pore formation during steam pore creation, preventing pore wall collapse and thus locking in high porosity. It also endows the membrane with ultra-high mechanical strength and thermal stability. Excessive PPTA is difficult to disperse uniformly and may aggregate, forming defects. Simultaneously, overly vigorous steam pore creation makes the PMIA matrix loose and porous, preventing the reinforcing effect of PPTA from being effectively utilized, leading to overall structural strength collapse. Therefore, the amount of PPTA nanofibers used, in conjunction with the steam jetting conditions, is more conducive to achieving a balance between high strength and high porosity.

[0041] More specifically, the specific operations in step S4 are as follows: the composite coating liquid is uniformly coated onto the release film using a comma-shaped doctor blade, followed by steam spraying to create pores, and then passing it through a coagulation bath (30%-40% DMAC aqueous solution), a water bath, and drying at 55-65℃, followed by winding. After winding, the aramid film is peeled off from the release film, and its mechanical properties are further improved by hot pressing, ultimately obtaining a meta-aramid-based separator with para-aramid nanofiber synergistic reinforcement.

[0042] More specifically, the hot pressing conditions are: temperature 80-120℃, pressure 40-80MPa, and time 3-7min.

[0043] More specifically, there are no strict restrictions on the release film used, as long as the coating liquid can be evenly applied to the release film and the aramid film can be easily peeled off.

[0044] A meta-aramid-based separator, wherein the meta-aramid-based separator is prepared according to the preparation method described in this invention.

[0045] Application of a meta-aramid-based separator, wherein the meta-aramid-based separator is used in a battery.

[0046] Example 1: Preparation of meta-aramid membrane.

[0047] A method for preparing a meta-aramid-based separator, wherein the preparation method comprises: (1) Alkali etching activation: Take PPTA nanofibers with a diameter of 50-200nm and a length of 0.1-1mm, add them to a 5wt% NaOH aqueous solution, stir at 60℃ for 2h; wash until pH=7, and vacuum dry at 80℃ for 4h.

[0048] (2) Organic acid grafting: The PPTA nanofibers treated in step (1) were added to a 10wt% citric acid aqueous solution (anhydrous citric acid was purchased from Shandong Yingxuan Industrial Co., Ltd., ≥99.5%), and stirred under reflux for 3 hours; filtered and washed until neutral, and dried under vacuum at 80°C for 4 hours to obtain modified PPTA nanofibers.

[0049] (3) Preparation of coating solution: DMAC was added to the meta-aramid stock solution and stirred for 2 hours to prepare a PMIA solution with a solid content of 5%; polyvinylpyrrolidone (PVP, Sichuan Tianhua Co., Ltd., ≥99.8%) was added and stirred for 15 minutes, with the amount of PVP added being 1 wt% of the mass of PMIA. Modified PPTA nanofibers (accounting for 5 wt% of the mass of PMIA) were added; high-speed shear dispersion at 15000 rpm for 20 minutes was performed, followed by ultrasonic dispersion at 300 W under an ice-water bath for 30 minutes to obtain the composite coating solution.

[0050] (4) Oil phase coating film formation: The slurry is evenly coated onto the release film using a comma-shaped doctor blade, followed by steam spraying to create pores. The steam concentration is 0.05 g / cm³. 2 The film is steam-treated for 5 seconds, then sequentially passed through a 35% DMAC coagulation bath, a water bath, dried at 60℃, and wound up. After winding, the aramid film is peeled off from the release film, and its mechanical properties are further improved by hot pressing at 80℃, 40 N / min, and 7 m / min. Finally, a meta-aramid-based membrane with para-aramid nanofiber synergistic reinforcement is obtained.

[0051] Example 2: Preparation of meta-aramid membrane.

[0052] A method for preparing a meta-aramid-based separator, wherein the preparation method comprises: (1) Alkali etching activation: Take PPTA nanofibers with a diameter of 50-200nm and a length of 0.1-1mm, add them to a NaOH aqueous solution with a mass concentration of 15wt%, stir at 80℃ for 4h; wash until pH=7, and vacuum dry at 80℃ for 4h.

[0053] (2) Organic acid grafting: The PPTA nanofibers treated in step (1) were added to a citric acid aqueous solution with a mass concentration of 20wt%, and stirred under reflux for 6h; filtered and washed until neutral, and dried under vacuum at 80℃ for 4h to obtain modified PPTA nanofibers.

[0054] (3) Preparation of coating solution: DMAC was added to the meta-aramid stock solution and stirred for 2 hours to prepare a PMIA solution with a solid content of 20%; PVP was added and stirred for 15 minutes, with the amount of PVP added being 5 wt% of the mass of PMIA. Modified PPTA nanofibers (accounting for 20 wt% of the mass of PMIA) were added; high-speed shear dispersion at 20,000 rpm for 30 minutes, and ultrasonic dispersion at 500 W in an ice-water bath for 60 minutes to obtain the composite coating solution.

[0055] (4) Oil phase coating film formation: The slurry is evenly coated onto the release film using a comma-shaped doctor blade, followed by steam spraying to create pores. The steam concentration is 0.2 g / cm³. 2 The film was steam-treated for 20 seconds, then sequentially passed through a 35% DMAC coagulation bath, dried at 60°C, and wound up. After winding, the aramid film was peeled off from the release film, and its mechanical properties were further improved by hot pressing at 120°C, 80 N / min, and 3 m / min. Finally, a meta-aramid-based membrane with para-aramid nanofiber synergistic reinforcement was obtained.

[0056] Example 3: Preparation of meta-aramid membrane.

[0057] A method for preparing a meta-aramid-based separator, wherein the preparation method comprises: (1) Alkali etching activation: Take PPTA nanofibers with a diameter of 50-200nm and a length of 0.1-1mm, add them to a 10wt% NaOH aqueous solution, stir at 70℃ for 3h; wash until pH=7, and vacuum dry at 80℃ for 4h.

[0058] (2) Organic acid grafting: The PPTA nanofibers treated in step (1) were added to a 15wt% citric acid aqueous solution and stirred under reflux for 5 hours; filtered and washed until neutral, and dried under vacuum at 80°C for 4 hours to obtain modified PPTA nanofibers.

[0059] (3) Preparation of coating solution: DMAC was added to the meta-aramid stock solution and stirred for 2 hours to prepare a PMIA solution with a solid content of 15%; PVP was added and stirred for 15 minutes, with the amount of PVP added being 3 wt% of the mass of PMIA. Modified PPTA nanofibers (accounting for 15 wt% of the mass of PMIA) were added; high-speed shear dispersion at 20,000 rpm for 30 minutes, and ultrasonic dispersion at 400 W in an ice-water bath for 50 minutes to obtain the composite coating solution.

[0060] (4) Oil phase coating film formation: The slurry is evenly coated onto the release film using a comma-shaped doctor blade, followed by steam spraying to create pores. The steam concentration is 0.15 g / cm³. 2 The film is steam-treated for 15 seconds, then sequentially passed through a 35% DMAC coagulation bath, a water bath, dried at 60℃, and wound up. After winding, the aramid film is peeled off from the release film, and its mechanical properties are further improved by hot pressing at 100℃, 50 N / min, and 5 m / min. Finally, a meta-aramid-based membrane with para-aramid nanofiber synergistic reinforcement is obtained.

[0061] Example 4: Preparation of meta-aramid membrane.

[0062] A method for preparing a meta-aramid-based separator, wherein the preparation method comprises: (1) Alkali etching activation: Take PPTA nanofibers with a diameter of 50-200nm and a length of 0.1-1mm, add them to a KOH aqueous solution with a mass concentration of 10wt%, stir at 70℃ for 3h; wash until pH=7, and vacuum dry at 80℃ for 4h.

[0063] (2) Organic acid grafting: The PPTA nanofibers treated in step (1) were added to a 12wt% tartaric acid aqueous solution and stirred under reflux for 6 hours; filtered and washed until neutral, and dried under vacuum at 80°C for 4 hours to obtain modified PPTA nanofibers.

[0064] (3) Preparation of coating solution: DMAC was added to the meta-aramid stock solution and stirred for 2 hours to prepare a PMIA solution with a solid content of 18%; Tween 80 was added and stirred for 15 minutes, with the amount of Tween 80 added being 4 wt% of the mass of PMIA. Modified PPTA nanofibers (accounting for 18 wt% of the mass of PMIA) were added; high-speed shear dispersion at 20,000 rpm for 30 minutes, and ultrasonic dispersion at 400 W in an ice-water bath for 50 minutes to obtain the composite coating solution.

[0065] (4) Oil phase coating film formation: The slurry is evenly coated onto the release film using a comma-shaped doctor blade, followed by steam spraying to create pores. The steam concentration is 0.18 g / cm³. 2The steam treatment time was 14s, followed by sequential passing through a 35% DMAC coagulation bath, a water bath, drying at 60℃, and winding. After winding, the aramid film was peeled off from the release film, and its mechanical properties were further improved by hot pressing at 100℃, a pressure of 50N / min, and a speed of 5m / min. Finally, a meta-aramid-based membrane with para-aramid nanofiber synergistic reinforcement was obtained.

[0066] Example 5: Preparation of meta-aramid membrane.

[0067] A method for preparing a meta-aramid-based separator, wherein the preparation method comprises: (1) Alkali etching activation: Take PPTA nanofibers with a diameter of 50-200nm and a length of 0.1-1mm, add them to a KOH aqueous solution with a mass concentration of 12wt%, stir at 80℃ for 2h; wash until pH=7, and vacuum dry at 80℃ for 4h.

[0068] (2) Organic acid grafting: The PPTA nanofibers treated in step (1) were added to an aqueous solution of 1,4-phthalic acid with a mass concentration of 20wt%, and stirred under reflux for 4h; filtered and washed until neutral, and dried under vacuum at 80℃ for 4h to obtain modified PPTA nanofibers.

[0069] (3) Preparation of coating solution: DMAC was added to the meta-aramid stock solution and stirred for 2 h to prepare a PMIA solution with a solid content of 15%; sodium dodecylbenzenesulfonate was added and stirred for 15 min, the amount of sodium dodecylbenzenesulfonate added was 2 wt% of the mass of PMIA. Modified PPTA nanofibers (accounting for 12 wt% of the mass of PMIA) were added; high-speed shear dispersion at 20000 rpm for 20 min, and ultrasonic dispersion at 500 W in an ice water bath for 50 min to obtain the composite coating solution.

[0070] (4) Oil phase coating film formation: The slurry is evenly coated onto the release film using a comma-shaped doctor blade, followed by steam spraying to create pores. The steam concentration is 0.15 g / cm³. 2 The film is steam-treated for 15 seconds, then sequentially passed through a 35% DMAC coagulation bath, a water bath, dried at 60℃, and wound up. After winding, the aramid film is peeled off from the release film, and its mechanical properties are further improved by hot pressing at 100℃, 50 N / min, and 5 m / min. Finally, a meta-aramid-based membrane with para-aramid nanofiber synergistic reinforcement is obtained.

[0071] Comparative Example 1: Conventional meta-aramid diaphragm.

[0072] Commercially available meta-aramid separators have a total thickness of 10 μm and a meta-aramid coating thickness of 3 μm.

[0073] Comparative Example 2: Preparation of the diaphragm.

[0074] Meta-aramid membranes were prepared using the same method as in Example 3, except that in Comparative Example 2, the PPTA nanofibers were not alkali-etched and activated or modified with organic acid grafting. Instead, the unmodified PPTA nanofibers were directly added to the PMIA solution to prepare the coating solution. Other process conditions were the same as in Example 1.

[0075] Comparative Example 3: Preparation of the diaphragm.

[0076] Meta-aramid membranes were prepared using the same method as in Example 3, except that: in this comparative example 3, the PPTA nanofibers were not activated by alkaline etching, that is, the operation of step (1) was not performed. Instead, the PPTA nanofibers were directly modified by organic acid grafting. Other process conditions were the same as in Example 1.

[0077] Comparative Example 4: Preparation of the diaphragm.

[0078] Meta-aramid membranes were prepared using the same method as in Example 3, except that: in this Comparative Example 4, the PPTA nanofibers were not modified by organic acid grafting, that is, the operation of step (2) was not performed. Instead, the PPTA nanofibers were directly used for the preparation of the coating solution after alkaline etching activation. Other process conditions were the same as in Example 1.

[0079] Comparative Example 5: Preparation of the diaphragm.

[0080] Meta-aramid membranes were prepared using the same method as in Example 3, except that the mass concentration of sodium hydroxide aqueous solution in Comparative Example 5 was 5 wt% and the mass concentration of citric acid aqueous solution was 20%, i.e., the mass concentration ratio of inorganic alkali solution to organic acid aqueous solution was 1:4.

[0081] Comparative Example 6: Preparation of the diaphragm.

[0082] Meta-aramid membranes were prepared using the same method as in Example 3, except that the mass concentration of sodium hydroxide aqueous solution in Comparative Example 6 was 15 wt% and the mass concentration of citric acid aqueous solution was 10%, i.e., the mass concentration ratio of inorganic alkali solution to organic acid aqueous solution was 1:0.67.

[0083] Comparative Example 7: Preparation of the diaphragm.

[0084] Meta-aramid-based membranes were prepared using the same method as in Example 3, except that the amount of modified PPTA nanofibers added in Comparative Example 7 was 1 wt% of PMIA (lower than the amount specified in this invention).

[0085] Comparative Example 8: Preparation of the diaphragm.

[0086] Meta-aramid membranes were prepared using the same method as in Example 3, except that the amount of modified PPTA nanofibers added in Comparative Example 8 was 25 wt% of PMIA (higher than the amount specified in this invention).

[0087] Comparative Example 9: Preparation of the diaphragm.

[0088] Meta-aramid membranes were prepared using the same method as in Example 3, except that in Comparative Example 9, the pores were created by steam spraying, with a steam concentration of 0.25 g / cm³. 2 (The amount of water vapor is higher than that specified in this invention).

[0089] Comparative Example 10: Preparation of the diaphragm.

[0090] Meta-aramid membranes were prepared using the same method as in Example 3, except that in Comparative Example 9, the pores were created by steam spraying, with a steam concentration of 0.02 g / cm³. 2 (Lower than the amount of water vapor specified in this invention).

[0091] The membranes prepared in the above embodiments and comparative examples were subjected to performance tests. The specific results are shown in Tables 1 and 2 below, and the test methods involved are as follows.

[0092] Thickness testing standard: GB / T 36363-2018; Porosity testing standard: T / CAAMTB 201-2024; Tensile strength testing standard: GB / T 36363-2018; Air permeability testing standard: GB / T 36363-2018; Heat shrinkage rate test standard: GB / T 36363-2018; Liquid absorption rate test standard: GB / T 13542.2-2009; Standard for membrane rupture temperature test: GB / T 36800.1-2018; Ionic conductivity testing standard: GB / T 36363-2018 (the specific test methods and requirements are described in detail in the standard).

[0093] Table 1 Performance test results of the diaphragm

[0094] Table 2 Comparison of ionic conductivity data for membranes

[0095] As can be seen from the data in Tables 1 and 2 above, the two-step modification of para-aramid nanofibers using the "alkali etching activation-organic acid grafting" method, combined with the stepwise dispersion process of "high-speed shearing-ultrasound," effectively solves the problems of easy agglomeration of nanofibers and poor interfacial bonding with the meta-aramid matrix. Simultaneously, the precise control of the pore structure is achieved through water vapor pore-forming and oil-phase coating film-forming processes, which helps to more accurately control the thickness and performance uniformity of the separator. The modified para-aramid nanofibers are uniformly dispersed in the meta-aramid matrix, forming a stable all-aramid composite system. The results of the examples show that the gas permeability and thermal stability of the separator are significantly improved, and the wettability of the electrolyte is also significantly enhanced, which helps to improve the cycle life and safety of lithium batteries, and is significantly superior to the conventional commercially available meta-aramid separator of Comparative Example 1. Figure 1 Here is an electron microscope image of the diaphragm prepared in Example 3. Figure 1 It can be seen that a uniform porous structure has been formed on the surface of the diaphragm.

[0096] A comparison of the experimental results from Comparative Example 2 and Example 3 shows that without alkaline etching activation and organic acid grafting modification of the PPTA nanofibers, the PPTA fibers and PMIA are only physically adsorbed together, lacking interfacial anchoring effects such as chemical bonding or hydrogen bonding. During the preparation of the coating solution, the unmodified PPTA fibers exhibit low surface polarity and a severe tendency to agglomerate. Even after high-speed shearing and ultrasonic dispersion, uniform dispersion within the PMIA matrix is ​​difficult to achieve. Ultimately, the PPTA fibers in the membrane exist primarily as aggregates, failing to exert the reinforcing effect of nanofibers. Furthermore, the aggregates themselves become stress concentration points and defect sources, leading to a significant decrease in the tensile strength, thermal shrinkage rate, and rupture temperature of the membrane.

[0097] A comparison of the experimental results from Comparative Example 3 and Example 3 shows that without alkaline etching activation of the PPTA nanofibers, the lack of hydroxyl and carboxyl groups and micro-rough structures introduced by alkaline etching on the PPTA fiber surface results in a severe shortage of reaction sites for organic acid grafting, leading to a significant reduction in both the efficiency and density of the grafting reaction. Although organic acid molecules can still adhere to the fiber surface through a small amount of hydrogen bonding, the grafting amount is extremely limited, failing to form a sufficiently dense carboxyl polar layer on the fiber surface. Consequently, the improvement in interfacial bonding between the modified fiber and the PMIA matrix is ​​limited. Therefore, the mechanical strength and thermal stability of the membrane decrease after the alkaline etching activation step is omitted.

[0098] A comparison of the experimental results from Comparative Example 4 and Example 3 shows that without organic acid grafting modification of the PPTA nanofibers, although alkaline etching activation can introduce a certain amount of polar groups such as carboxyl and hydroxyl groups onto the fiber surface and form a micro-rough structure, the number and surface coverage density of these newly formed polar groups are limited, and there is a lack of further amplification and supplementation from subsequent grafting reactions. The polar groups introduced solely by alkaline etching activation are insufficient to form an interface layer on the fiber surface that is sufficiently chemically bonded to the PMIA matrix. The interfacial bonding between PPTA fibers and PMIA remains primarily physical adsorption, with insufficient chemical bonding. Therefore, the tensile strength and rupture temperature of the membrane are significantly lower than in Example 3. This demonstrates that the combined surface modification steps of "alkaline etching activation" and "organic acid grafting" play a crucial role in achieving effective interfacial bonding between PPTA fibers and the PMIA matrix.

[0099] A comparison of the experimental results from Comparative Example 5 and Example 3 shows that if the mass concentration ratio of the inorganic alkali solution to the organic acid aqueous solution is 1:4, meaning the organic acid concentration is relatively high compared to the alkali concentration, the number of active sites generated on the fiber surface during the alkali etching activation step is limited. However, the number of grafted molecules provided during the organic acid grafting step far exceeds the upper limit that the active sites can accommodate. Excess organic acid molecules cannot all be grafted onto the fiber surface through chemical bonds; most can only adhere to the fiber surface through physical adsorption, making them easily removed during subsequent washing. This not only wastes raw materials but also, the residual physically adsorbed organic acid may interfere with the dispersion of the fiber in the coating solution, thus affecting the membrane performance.

[0100] A comparison of the experimental results from Comparative Example 6 and Example 3 shows that when the mass concentration ratio of the inorganic alkaline solution to the organic acid aqueous solution is 1:0.67, although alkaline etching activation provides sufficient active sites on the fiber surface, the supply of grafting molecules in the organic acid grafting step is insufficient. A large number of active sites fail to be occupied by organic acid molecules, and the grafting reaction is far from saturated. The carboxyl grafting density on the fiber surface is low, and the number of chemical bonding points between the PPTA fiber and the PMIA matrix is ​​insufficient, limiting the improvement of interfacial bonding. Therefore, the mechanical strength and thermal stability of the membrane are slightly lower than in Example 3. This further verifies that a reasonable match between the alkali concentration and the acid concentration is more conducive to achieving a balance between the number of active sites and the supply of grafting molecules, resulting in a better interfacial modification effect.

[0101] A comparison of the experimental results from Comparative Example 7 and Example 3 shows that if the amount of modified PPTA nanofibers added is too small, the dispersion density of the PPTA nanofibers in the PMIA matrix is ​​too low, making it impossible to form a continuous and complete three-dimensional support framework structure. Although a small amount of reinforcing fibers are present in the membrane, their spacing is too large, and there is a lack of sufficient rigid support points around the pore walls. The pore structure formed during the water vapor pore-forming process is prone to shrinkage and collapse, resulting in a significant increase in the thermal shrinkage rate of the membrane and limited improvement in mechanical strength. This fails to achieve the technical effect of combining high porosity and high strength as described in this invention. This indicates that when the amount of PPTA added is below the lower limit, the framework support effect is insufficient to play a substantial reinforcing role.

[0102] A comparison of the experimental results from Comparative Example 8 and Example 3 shows that if too much modified PPTA nanofiber is added, the excess nanofibers are prone to self-aggregation in the coating solution. Even after high-speed shearing and ultrasonic dispersion, it is difficult to completely break up the agglomerates. These fiber agglomerates become defects inside the membrane after film formation, which not only fail to effectively transfer the load but also lead to stress concentration, causing a sharp decrease in the tensile strength of the membrane. At the same time, the excessively dense fiber network may interfere with the phase transformation and pore formation process of the PMIA matrix, resulting in uneven pore structure, poor permeability, and deterioration of air permeability and ionic conductivity.

[0103] A comparison of the experimental results from Comparative Example 9 and Example 3 shows that if the amount of water vapor increases, excessive water vapor will invade the casting solution in a short period of time, causing the PMIA phase transformation process to be too violent and rapid. Violent phase separation causes the polymer to solidify rapidly, resulting in a coarse and uneven pore structure with thin and fragile pore walls. At the same time, the shrinkage stress generated by violent pore formation increases significantly, and the supporting framework of modified PPTA nanofibers cannot completely resist the excessive shrinkage stress. The overall structure of the membrane undergoes irreversible shrinkage, the thermal shrinkage rate increases significantly, and the mechanical strength decreases significantly.

[0104] A comparison of the experimental results from Comparative Example 10 and Example 3 shows that if the amount of water vapor decreases, the water vapor intrusion is severely insufficient, the driving force for PMIA phase transformation is extremely limited, only a very small area in the casting solution undergoes phase separation, and most areas remain dense, resulting in extremely low membrane porosity. Low porosity means a severe lack of lithium-ion transport channels, a significant increase in permeability, and a significant decrease in ionic conductivity, causing the membrane to lose its expected ion transport function as a lithium-ion battery membrane. This indicates that when the water vapor content is below the lower limit, the pore-forming effect cannot be effectively achieved, and the electrochemical performance of the membrane cannot meet application requirements.

[0105] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0106] For those skilled in the art, various modifications and improvements can be made without departing from the concept of the present invention, and these modifications and improvements are all within the scope of protection of the present invention. The scope of protection of the present invention is defined by the appended claims.

Claims

1. A method for preparing a meta-aramid-based separator, characterized in that, The preparation method is as follows: S1. Alkali etching activation: PPTA nanofibers are added to an inorganic alkaline solution for alkaline etching activation, followed by washing and drying; S2, Organic acid grafting: The PPTA nanofibers treated in step S1 are added to an organic acid aqueous solution to carry out an organic acid grafting reaction, and then washed and dried to obtain modified PPTA nanofibers. S3. Preparation of coating solution: Add the modified PPTA nanofibers to the PMIA solution containing the dispersant and perform sufficient dispersion treatment to obtain a uniform composite coating solution. S4. Coating and film formation: The composite coating liquid is uniformly coated on the release film, water vapor is sprayed to create holes, and then the film is sequentially passed through a coagulation bath, a water bath, drying, and winding. The aramid film is peeled off from the release film, and the aramid film is hot-pressed to obtain the meta-aramid-based diaphragm. The mass concentration ratio of the inorganic alkaline solution to the organic acid aqueous solution is 1:(1.3-2.0). In step S3, the amount of modified PPTA nanofibers added is 5-20 wt% of the PMIA mass. In step S4, the conditions for the water vapor spray film pore formation are: water vapor quantity of 0.05-0.2 g / cm², and steam action time of 5-20 s.

2. The method for preparing a meta-aramid-based separator according to claim 1, characterized in that, In step S1, the inorganic alkaline solution is at least one of sodium hydroxide aqueous solution and potassium hydroxide aqueous solution, and the mass concentration of the inorganic alkaline solution is 5-15 wt%. In step S1, during the alkaline etching and activation process, the temperature is 60-80℃, and the mixture is stirred at a constant temperature for 2-4 hours.

3. The method for preparing a meta-aramid-based separator according to claim 1, characterized in that, In step S2, the organic acid aqueous solution is at least one selected from citric acid aqueous solution, tartaric acid aqueous solution, and 1,4-phthalic acid aqueous solution, and the mass concentration of the organic acid aqueous solution is 10-20 wt%. In step S2, the organic acid grafting reaction is completed by stirring under reflux for 3-6 hours.

4. The method for preparing a meta-aramid-based separator according to claim 1, characterized in that, In step S3, the solid content of the PMIA solution is 5-20 wt%.

5. The method for preparing a meta-aramid-based separator according to claim 1, characterized in that, In step S3, the dispersant is at least one of polyvinylpyrrolidone, sodium dodecylbenzenesulfonate, and Tween 80; the amount of the dispersant added is 1-5 wt% of the PMIA mass.

6. The method for preparing a meta-aramid-based separator according to claim 1, characterized in that, In step S3, the dispersion process includes high-speed shear dispersion and ultrasonic dispersion performed sequentially; the high-speed shear dispersion has a rotation speed of 15,000-20,000 rpm and a dispersion time of 20-30 min; the ultrasonic dispersion has a power of 300-500 W and a dispersion time of 30-60 min, and the ultrasonic dispersion is performed under ice-water bath conditions.

7. A meta-aramid-based separator, characterized in that, The meta-aramid membrane is prepared according to the preparation method described in any one of claims 1-6.

8. An application of the meta-aramid membrane according to claim 7, characterized in that, The meta-aramid-based separator is used in batteries.

Citation Information

Patent Citations

  • Modified composite heat-resistant lithium ion battery diaphragm and preparation method thereof

    CN112216928A

  • Aramid fiber lithium battery diaphragm with low closed pore and high diaphragm rupture and preparation method of aramid fiber lithium battery diaphragm

    CN115275505A